Taṭwīr Kitāb al-Lughat al-‘Arabiyyat ‘ala Asās al-Dzakā’at al-Muta’addidat Bi al-Taṭbīq ‘ala al-Madrasat al-Ibtidāiyyat al-Islamiyyat al-‘Alamiyyat Mālanj - Muhimmatul Mukaromah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
This study aims to determine the development of Arabic language textbooks based on Multiple Intelligences at the Madrasah Ibtidaiyah/Islamic Elementary School level and the effectiveness of their use in the classroom. This research is based on the problem finding that some of the textbooks used in some schools are still less effective for learning Arabic. In some Arabic textbooks at the Madrasah Ibtidaiyah/Islamic Elementary School level, there are many long texts for learning istima', kalam, and qiro'ah so that they are not suitable for basic level learners. Some books focus only on the cognitive domain, and do not accommodate various types of intelligence so that they are less helpful for students to develop. This study uses Research and Development (R&D) research methods and data collection is carried out by observation, interviews, questionnaires, and tests. The test subjects consisted of content experts, instructional design experts, textbook design experts, and grade 3B students of SD Islamic Global School Malang as the target users of the product. The results of this study indicate: 1) Multiple Intelligences-based Arabic textbooks were developed based on needs analysis and field data, then designed in the form of an initial draft to be tested by three experts, then revised and tested individually, and field tested on grade 3B students. SD Islamic Global School Malang. The second and third stage revisions were carried out after the trial process. The revised result is the final product of this research, 2) The use of the the book "Lughati Mumtazah" in 3B class of Islamic Global Elementary School Malang were proven effectively. This is due to the evidence that statistical results of (t) between the two classes (5.03) greater than t-table value at 0.05 level (1.74) and at the 0.01 level (2.56), so the hypothesis is accepted, and this condition shows that the use of the book "Lughati Mumtazah" is so effective. Abstrak Penelitian ini bertujuan untuk mengetahui pengembangan buku ajar bahasa Arab berbasis Multiple Intelligences di tingkat Madrasah Ibtidaiyah/Sekolah Dasar Islam dan efektifitas penggunaannya di kelas. Hal ini didasarkan pada temuan permasalahan bahwa beberapa buku ajar yang digunakan di beberapa sekolah masih kurang efektif untuk belajar bahasa Arab. Dalam beberapa buku ajar bahasa Arab di tingkat Madrasah Ibtidaiyah/Sekolah Dasar Islam terdapat banyak teks yang panjang untuk pembelajaran istima’, kalam, dan qiro’ah sehingga kurang sesuai dengan pembelajar tingkat dasar. Beberapa buku terfokus hanya pada domain kognitif saja, dan tidak mengakomodir berbagai jenis kecerdasan sehingga kurang membantu siswa untuk berkembang. Studi ini menggunakan metode penelitian Research and Development (R&D) dan pengumpulan data dilakukan dengan observasi, wawancara, angket, dan tes. Subjek uji coba terdiri dari ahli isi, ahli desain pembelajaran, ahli desain buku ajar, dan siswa kelas 3B SD Islamic Global School Malang sebagai sasaran pemakai produk. Hasil penelitian ini menunjukkan: 1) Buku ajar bahasa Arab berbasis Multiple Intelligences dikembangkan berdasarkan analisis kebutuhan dan data lapangan, kemudian didesain dalam bentuk draft awal untuk diuji coba oleh tiga ahli, kemudian direvisi dan diuji cobakan secara perseorangan, dan diuji lapangan pada siswa kelas 3B SD Islamic Global School Malang. Revisi tahap kedua dan ketiga dilakukan setelah proses uji coba tersebut. Hasil revisi merupakan produk akhir dari penelitian ini, 2) penggunaan buku “Lughati Mumtazah” di kelas 3B SD Islamic Global School Malang berjalan efektif. Hal ini ditunjukkan dengan bukti bahwa hasil statistik (t) antara kedua kelas (5,03) lebih besar dari nilai t-tabel pada taraf 0,05 (1,74) dan pada taraf 0,01 (2,56), sehingga hipotesis diterima, hal ini menunjukkan bahwa penggunaan buku "Lughati Mumtazah" sangat efektif